Supported metallocene catalyst and preparation method and application thereof

By using spherical mesoporous clay composite materials made of mesoporous clay silica, silica gel and leaf sac clay minerals as support, metallocene compounds and alkyl aluminoxanes, the problem of low activity of mesoporous MCM-41 supported metallocene catalysts is solved, and a supported metallocene catalyst with stable structure and high catalytic activity is achieved, which significantly improves the efficiency of olefin polymerization.

CN119874966AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311378797.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25
Estimated Expiration
2043-10-23

Smart Images

  • Figure CN119874966A_ABST
    Figure CN119874966A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of olefin polymerization, and discloses a supported metallocene catalyst and a preparation method and application thereof, the catalyst comprises a carrier, and a metallocene compound and alkyl aluminoxane which are supported on the carrier; the carrier is a three-dimensional cubic pore channel spherical pyrophyllite clay mineral mesoporous clay composite material prepared from mesoporous clay silicon dioxide, silica gel and pyrophyllite clay mineral; the metallocene compound has a structure as shown in a formula 1, in the # imgabs0 # formula 1, R1, R2, R3, R4, R5, R1 ', R2', R3 ', R4' and R5'are respectively and independently hydrogen or C1-C5 alkyl, at least one of R1, R2, R3, R4 and R5 is C1-C5 alkyl, at least one of R1 ', R2', R3 ', R4' and R5 'is C1-C5 alkyl, M is one of titanium, zirconium and hafnium, and X is halo.The catalyst is stable in structure and high in catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of olefin polymerization, and in particular relates to a supported metallocene catalyst and a preparation method and application thereof. Background Art

[0002] The development and application of metallocene catalyst is after traditional Ziegler-Natta catalyst, another major breakthrough in the field of olefin polymerization catalyst, particularly the eighties, Kaminsky and Sinn et al. developed efficient cocatalyst methylaluminoxane (MAO), so that the research of metallocene catalyst has entered a stage of rapid development. Because homogeneous metallocene catalyst reaches the required MAO consumption of high activity, the production cost is high, and the polymer obtained has no granular shape, it is impossible to use on widely used slurry process or gas phase polymerization technology, and the effective way to solve the above problem is exactly that soluble metallocene catalyst is carried out to loading treatment. At present, relevant metallocene loading research report is very much, wherein with SiO as 955 silica gel is the most reported research of carrier, for example patent documentation CN1095474C, CN1049439C, CN1157419C, US4808561, US5026797, US5763543, US5661098 all disclose with SiO as the loaded metallocene catalyst of carrier. In order to further study new carrier / catalyst / co-catalyst systems, it is necessary to try different carriers to promote the further development of supported catalysts and polyolefin industry.

[0003] Loading olefin polymerization catalyst on molecular sieve has the following advantages:

[0004] (1) Artificially synthesized molecular sieves do not contain impurities that can easily degrade polymers, and will improve the anti-aging properties of polyolefin materials;

[0005] (2) The molecular sieve nanopores have the dual functions of carrier and reactor, with high catalyst loading efficiency, easy control of the polymerization process, and can be inserted into the skeleton of the polymerization reactor to accelerate the reaction process and improve the yield;

[0006] (3) It has a stereoselective effect on monomer insertion and polymerization reactions, and can increase the molecular weight and melting point of polyolefins.

[0007] It can be seen that the emergence of molecular sieve-supported olefin polymerization catalysts has opened up a new field for olefin coordination polymerization.

[0008] At present, there are literature reports on using MAO-treated MCM-41 mesoporous materials to load metallocene catalysts to catalyze olefin polymerization, but the activity of catalytic ethylene polymerization is only 10 6g PE / (mol Zr h) (Chen ST, Guo CY, Lei L, et al. Polymer, 2005, 46: 11093).

[0009] Patent document CN1923862 discloses a mesoporous molecular sieve supported olefin polymerization catalyst, which is obtained by supporting a semi-sandwich metallocene compound shown in the following formula on SBA-15 treated with MAO:

[0010]

[0011] However, the catalytic activity of the catalyst disclosed in patent document CN1923862 is only 10 6 g PE / (mol Zrh).

[0012] Therefore, how to obtain supported metallocene catalysts with high catalytic activity remains a technical problem that needs to be solved urgently. Summary of the invention

[0013] In view of the above problems existing in the prior art, the object of the present invention is to provide a supported metallocene catalyst and a preparation method and application thereof, wherein the prepared catalyst has a stable structure and high activity when used for olefin polymerization.

[0014] The inventors of the present invention have found that the main reason why the mesoporous material MCM-41 has low ethylene polymerization activity after loading metallocene is that the thermal stability and hydrothermal stability of the pore wall structure of MCM-41 are poor. During the loading process, the pore wall partially collapses, affecting the loading effect and even the catalytic activity. Therefore, the present invention seeks a carrier with a stable mesoporous structure that can still maintain an orderly mesoporous structure after loading.

[0015] The geometric shape of spherical mesoporous materials has obvious advantages in reducing powder agglomeration and improving its fluidity. Therefore, making mesoporous materials into spheres can not only retain the characteristics of high specific surface area, large pore volume, large pore size and narrow distribution of mesoporous materials, but also reduce the agglomeration of mesoporous materials and increase their fluidity.

[0016] Pyrophyllite is a layered clay mineral, a hydrous aluminum silicate pyrophyllite mineral. It is a very promising functional clay mineral due to its low cost, good insulation, acid resistance, and low hardness.

[0017] Based on the above findings, the inventors of the present invention combined pyrophyllite with mesoporous materials and the like to obtain the supported metallocene catalyst carrier of the present invention, which has a stable mesoporous structure and a well-dispersed, complete spherical microstructure.

[0018] The first aspect of the present invention provides a supported metallocene catalyst, which comprises a carrier and a metallocene compound and an alkylaluminoxane supported on the carrier; the carrier is a spherical pyrophyllite clay mineral mesoporous clay composite material with three-dimensional cubic channels made of mesoporous clay silica, silica gel and pyrophyllite clay mineral; the metallocene compound has a structure shown in Formula 1,

[0019]

[0020] In Formula 1, R1, R2, R3, R4, R5, R1', R2', R3', R4' and R5' are each independently hydrogen or a C1-C5 alkyl group, and at least one of R1, R2, R3, R4 and R5 is a C1-C5 alkyl group, at least one of R1', R2', R3', R4' and R5' is a C1-C5 alkyl group, M is one of titanium, zirconium and hafnium, and X is a halogen.

[0021] The second aspect of the present invention provides a method for preparing the above-mentioned supported metallocene catalyst, the preparation method comprising the following steps:

[0022] (1) contacting the carrier with alkylaluminoxane in a solvent under the protection of an inert gas, and then removing the solvent to obtain a carrier loaded with alkylaluminoxane;

[0023] (2) Under the protection of an inert gas, the carrier loaded with alkylaluminoxane is contacted with a metallocene compound in a solvent, and the solvent is removed to obtain the supported metallocene catalyst.

[0024] The third aspect of the present invention provides the use of the above-mentioned supported metallocene catalyst in olefin polymerization.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The carrier mesoporous structure of the supported metallocene catalyst of the present invention is stable, and the microscopic morphology is a complete sphere with good dispersibility. The supported metallocene catalyst obtained has a stable structure and is used for olefin polymerization with high catalytic activity.

[0027] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope photograph of the carrier prepared in Example 1.

[0029] Figure 2 This is the X-ray diffraction pattern of the carrier prepared in Example 1. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] According to the first aspect of the present invention, the present invention provides a supported metallocene catalyst, which comprises a carrier and a metallocene compound and an alkylaluminoxane supported on the carrier; the carrier is a spherical pyrophyllite clay mineral mesoporous clay composite material with three-dimensional cubic channels made of mesoporous clay silica, silica gel and pyrophyllite clay mineral; the metallocene compound has a structure shown in Formula 1,

[0032]

[0033] In Formula 1, R1, R2, R3, R4, R5, R1', R2', R3', R4' and R5' are each independently hydrogen or a C1-C5 alkyl group, and at least one of R1, R2, R3, R4 and R5 is a C1-C5 alkyl group, at least one of R1', R2', R3', R4' and R5' is a C1-C5 alkyl group, M is one of titanium, zirconium and hafnium, and X is a halogen.

[0034] According to the present invention, in Formula 1, the cyclopentadienyl group is a group that can form an η 5 The derivative of the cyclopentadienyl anion having a C1-C5 alkyl group and a cyclopentadienyl anion having a C1-C5 alkyl group can be one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl and neopentyl.

[0035] Specific examples of the cyclopentadienyl group include methylcyclopentadienyl, 1,2-dimethyl-cyclopentadienyl, 1,3-dimethyl-cyclopentadienyl, 1,2,3-trimethyl-cyclopentadienyl, 1,2,4-trimethyl-cyclopentadienyl, 1,2,3,4-tetramethyl-cyclopentadienyl, pentamethylcyclopentadienyl, ethylcyclopentadienyl, 1,2-diethyl-cyclopentadienyl, 1,3-diethyl-cyclopentadienyl, 1,2,4-triethyl-cyclopentadienyl, Cyclopentadienyl, 1,3,5-triethyl-cyclopentadienyl, 1-methyl-2-ethyl-cyclopentadienyl, 1-methyl-3-ethyl-cyclopentadienyl, n-propyl-cyclopentadienyl, isopropyl-cyclopentadienyl, 1,3-di-n-propyl-cyclopentadienyl, 1-methyl-3-n-propyl-cyclopentadienyl, 1,3-diisopropyl-cyclopentadienyl, 1-methyl-3-isopropyl-cyclopentadienyl, n-butyl-cyclopentadienyl, sec-butyl-cyclopentadienyl, Isobutylcyclopentadienyl, tert-butylcyclopentadienyl, 1,3-di-n-butyl-cyclopentadienyl, 1-methyl-3-n-butyl-cyclopentadienyl, 1,3-di-sec-butyl-cyclopentadienyl, 1-methyl-3-sec-butyl-cyclopentadienyl, 1,3-diisobutyl-cyclopentadienyl, 1-methyl-3-isobutyl-cyclopentadienyl, 1,3-di-tert-butyl-cyclopentadienyl, 1-methyl-3-tert-butyl-cyclopentadienyl, n-pentylcyclopentadienyl, isobutylcyclopentadienyl, tert-butylcyclopentadienyl, 1- ... Pentylcyclopentadienyl, tert-pentylcyclopentadienyl, neopentylcyclopentadienyl, 1,3-di-n-pentyl-cyclopentadienyl, 1-methyl-3-n-pentyl-cyclopentadienyl, 1,3-diisopentyl-cyclopentadienyl, 1-methyl-3-isopentyl-cyclopentadienyl, 1,3-di-tert-pentyl-cyclopentadienyl, 1-methyl-3-tert-pentyl-cyclopentadienyl, 1,3-dineopentyl-cyclopentadienyl, 1-methyl-3-neopentyl-cyclopentadienyl.

[0036] Preferably, R1 and R1' are each independently a C1-C5 alkyl group, and R2, R3, R4, R5, R2', R3', R4' and R5' are all hydrogen. Specific examples of cyclopentadienyl include: methylcyclopentadienyl, ethylcyclopentadienyl, n-propylcyclopentadienyl, isopropylcyclopentadienyl, n-butylcyclopentadienyl, sec-butylcyclopentadienyl, isobutylcyclopentadienyl, tert-butylcyclopentadienyl, n-pentylcyclopentadienyl, isopentylcyclopentadienyl, tert-pentylcyclopentadienyl and neopentylcyclopentadienyl.

[0037] Further preferably, R1 and R1' are each independently n-butyl or tert-butyl, and more preferably, R1 and R1' are both n-butyl.

[0038] According to the present invention, M in different metallocene compound molecules may be the same or different. Preferably, M is zirconium.

[0039] According to the present invention, X in Formula 1 can be one of fluorine, chlorine, bromine and iodine. X in different metallocene compound molecules can be the same or different. Preferably, X in Formula 1 is chlorine or bromine. More preferably, X in Formula 1 is chlorine.

[0040] Preferably, the metallocene compound is bis(n-butylcyclopentadienyl)zirconium dichloride.

[0041] In the present invention, the alkylaluminoxane can be various alkylaluminoxanes commonly used in the field of metallocene catalysts. Generally, the alkyl group in the alkylaluminoxane is a C1-C5 alkyl group, and the C1-C5 alkyl group can be the various C1-C5 alkyl groups mentioned above. Preferably, the alkylaluminoxane is methylaluminoxane.

[0042] According to the present invention, the carrier has an average particle size of 30-60 microns, a specific surface area of ​​150-600 square meters / gram, a pore volume of 0.5-1.5 milliliters / gram, and a most probable pore size of 2-4, 5-15 and 10-40 nanometers.

[0043] The carrier of the present invention is made of mesoporous clay silica, silica gel and pyrophyllite clay mineral, and has a three-pore distribution structure. The three-pore distribution structure is provided by the mesoporous clay silica and silica gel. A spherical carrier with the above-mentioned pore size structure can be obtained by controlling the synthesis and molding methods. The use of pyrophyllite clay mineral helps to improve the activity of the catalyst.

[0044] According to a specific embodiment, the method for preparing the carrier comprises the following steps:

[0045] 1) in the presence of a template, trimethylpentane and ethanol, tetramethoxysilane is contacted with an acid agent, and the product obtained after the contact is crystallized and filtered to obtain a mesoporous clay silica filter cake No. 1; hexadecyltrimethylammonium bromide, ethyl orthosilicate and ammonia water are contacted, and the product after the contact is filtered to obtain a mesoporous clay silica filter cake No. 2;

[0046] 2) contacting water glass with an inorganic acid, and filtering the product obtained after the contact to obtain a silica gel filter cake;

[0047] 3) mixing and ball-milling the No. 1 mesoporous clay silica filter cake, the No. 2 mesoporous clay silica filter cake, the silica gel filter cake and the pyrophyllite clay mineral powder;

[0048] 4) The solid powder obtained after ball milling is slurried with water and then spray-dried, and then the template in the obtained product is removed to obtain the carrier.

[0049] In step 1) of the present invention, there is no particular limitation on the type of the template, as long as the carrier can have the above-mentioned pore structure. Preferably, the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene. The template can be commercially available (for example, it can be purchased from Aldrich Company, with the trade name P123), or can be prepared by various existing methods.

[0050] In step 1) of the present invention, there is no particular limitation on the type of the acid agent, which can be a conventional choice in the art, and can be various existing acids or acid mixtures. The acid or acid mixture can be used in a pure state or in the form of an aqueous solution, preferably in the form of an aqueous solution. Preferably, the acid agent is a buffer solution of acetic acid and sodium acetate with a pH value of 1-6 (preferably 3-5).

[0051] According to the present invention, the molar ratio of the template, ethanol, trimethylpentane and tetramethoxysilane can be 1:100-500:200-600:50-200, preferably 1:200-400:250-400:70-150.

[0052] According to the present invention, the molar ratio of ammonia to water in the tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia water can be 1:0.1-1:0.1-5:100-200, preferably 1:0.1-0.5:2-4:120-160.

[0053] In the present invention, the conditions for contacting tetramethoxysilane with an acid agent may include: a temperature of 10-60°C, a time of 10-72 hours, and a pH value of 1-7. Preferably, the conditions for contacting tetramethoxysilane with an acid agent include: a temperature of 10-30°C, a time of 20-40 hours, and a pH value of 3-6. In order to be more conducive to uniform mixing of the various substances, the contact of the tetramethoxysilane with the acid agent is preferably carried out under stirring conditions. The conditions for crystallization may include: a temperature of 30-150°C, and a time of 10-72 hours. Preferably, the conditions for crystallization include: a temperature of 40-80°C, and a time of 20-40 hours.

[0054] In the present invention, the conditions for contacting hexadecyltrimethylammonium bromide, ethyl orthosilicate and ammonia water may include: temperature of 25-100° C., time of 1-10 hours. Preferably, the contact temperature is 50-100° C., and the contact time is 2-6 hours.

[0055] The present invention does not particularly limit the contacting mode between the template agent, ethanol, acid agent, trimethylpentane and tetramethoxysilane. For example, the above five substances can be mixed and contacted simultaneously, or several substances can be mixed and contacted first, and then the remaining substances are added to the obtained mixture and continued to be mixed and contacted. Preferably, the template agent, ethanol, acidic aqueous solution and trimethylpentane are first stirred and mixed, and then tetramethoxysilane is added and continued to be stirred and mixed.

[0056] According to the present invention, in step 2), the inorganic acid may be one or more of sulfuric acid, nitric acid and hydrochloric acid.

[0057] The conditions for contacting the water glass with the inorganic acid may include: a temperature of 10-60° C., a time of 1-5 hours, and a pH value of 2-4. Preferably, the temperature is 20-40° C., and the time is 1.5-3 hours.

[0058] In step 3) of the present invention, based on 100 parts by weight of the total amount of the No. 1 mesoporous clay silica filter cake and the No. 2 mesoporous clay silica filter cake, the amount of the silica gel filter cake is 20-150 parts by weight, and the amount of the pyrophyllite clay mineral powder is 20-150 parts by weight. The weight ratio of the No. 1 mesoporous clay silica filter cake to the No. 2 mesoporous clay silica filter cake can be 0.5-1.5:1.

[0059] In the present invention, there is no particular limitation on the specific operation method and conditions of ball milling, provided that the structure of the carrier is not destroyed or substantially not destroyed. Those skilled in the art can select various suitable conditions to implement the present invention according to the above principles. Specifically, the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball milling jar, and for a ball milling jar of 50-150 mL in size, usually one grinding ball can be used; the material of the grinding balls can be agate, polytetrafluoroethylene, etc., preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 300-500 r / min, the temperature in the ball milling jar can be 15-100°C, and the ball milling time can be 0.1-100 hours.

[0060] In the present invention, the specific operation method and conditions of the spray drying are well known to those skilled in the art. Specifically, a slurry composed of the solid powder and water is added to an atomizer and rotated at high speed to achieve spray drying. Among them, the conditions for spray drying include: the temperature can be 100-300°C, and the rotation speed can be 10000-15000r / min; preferably, the conditions for spray drying include: the temperature is 150-250°C, and the rotation speed is 11000-13000r / min; most preferably, the conditions for spray drying include: the temperature is 200°C, and the rotation speed is 12000r / min.

[0061] In the present invention, the method for removing the template agent can be a calcination method, and the calcination conditions include: the temperature can be 500-700°C, preferably 500-600°C; the time can be 10-40 hours, preferably 20-30 hours, and most preferably 24 hours.

[0062] According to the present invention, the amount of the metallocene compound and the alkylaluminoxane loaded on the carrier can be changed in a wide range. The inventors of the present invention have found that when the total amount of the metallocene compound and the alkylaluminoxane is 10-60% by weight and the content of the carrier is 40-90% by weight based on the total weight of the supported metallocene catalyst, not only a satisfactory catalytic effect can be obtained, but also the cost can be reduced. More preferably, when the total weight of the supported metallocene catalyst is 45-55% by weight and the content of the carrier is 45-55% by weight, it should be clear that the content of the metallocene compound, the alkylaluminoxane and the carrier in the catalyst is calculated according to the weight of the raw materials of each component before loading.

[0063] In the present invention, the ratio between the alkylaluminoxane and the metallocene compound can be a ratio known to those skilled in the art of olefin polymerization. Specifically, the molar ratio of aluminum in the alkylaluminoxane to M in the metallocene compound can be 10-300:1, preferably 15-250:1, and more preferably 15-200:1.

[0064] According to a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned supported metallocene catalyst, the preparation method comprising the following steps:

[0065] (1) contacting the carrier with alkylaluminoxane in a solvent under the protection of an inert gas, and then removing the solvent to obtain a carrier loaded with alkylaluminoxane;

[0066] (2) Under the protection of an inert gas, the carrier loaded with alkylaluminoxane is contacted with a metallocene compound in a solvent, and the solvent is removed to obtain the supported metallocene catalyst.

[0067] The present invention has no particular limitation on the contact method, and may be any method known to those skilled in the art, such as dipping or spraying. The dipping method allows the solution to more fully enter the pores on the carrier, and therefore, dipping is preferred in the present invention.

[0068] In the present invention, the contact conditions in step (1) include: contact time of 1-10 hours, preferably 2-6 hours, more preferably 4 hours; contact temperature of 25-80°C, preferably 30-60°C, more preferably 50°C.

[0069] According to the present invention, the contact conditions in step (2) include: contact time of 0.3-2 hours, preferably 0.4-1 hours, more preferably 0.5 hours; contact temperature of 25-80°C, preferably 25-50°C, more preferably 30°C.

[0070] In the present invention, the amount of the carrier, alkylaluminoxane and metallocene compound can be adjusted and determined according to the content of each component in the above-mentioned catalyst.

[0071] According to the present invention, the solvent may be a conventional solvent, such as toluene, and is preferably refined by a method known to those skilled in the art before use to remove water and the like.

[0072] The preparation method of the present invention may also include heating the carrier at a temperature of 300-900° C. for 7-36 hours under inert gas protection before loading the alkylaluminoxane and the metallocene compound to remove hydroxyl groups on the surface of the carrier and volatile substances (such as water) contained in the carrier.

[0073] According to the present invention, the inert gas may be any gas that does not chemically interact with the carrier, alkylaluminoxane, or metallocene compound. For example, the inert gas may be nitrogen or argon, preferably nitrogen.

[0074] According to the third aspect of the present invention, the present invention provides a use of the above-mentioned supported metallocene catalyst in olefin polymerization.

[0075] The supported metallocene catalyst of the present invention is a catalyst with stable structure and high catalytic activity. When used in ethylene homopolymerization and copolymerization, it exhibits high activity.

[0076] The substances and parameters not limited in the present invention can be selected according to the prior art and belong to the conventional technical means in the field. Unless otherwise specified, the operations and processing methods involved in the present invention belong to the conventional methods in the field, the instruments used are conventional instruments in the field, and the raw materials used are commercially available.

[0077] The present invention will be further described below with reference to the following examples, but is not limited to these examples.

[0078] In the following examples and comparative examples, the sources of the raw materials and the determination methods of the data are as follows:

[0079] Triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene: purchased from Aldrich Company, P123;

[0080] Methylaluminoxane: purchased from Albemarle, USA, with an average molecular weight Mn of 5800;

[0081] Bis(n-butylcyclopentadienyl)zirconium dichloride: purchased from Alfa Aesar, product number H27576;

[0082] Triethylaluminum: TEA, purchased from Zhejiang Freed Chemical Co., Ltd.;

[0083] ES955 silica gel: purchased from GRACE.

[0084] 1. X-ray diffraction analysis was performed on an X-ray diffractometer model D8 Advance purchased from Bruker AXS, Germany.

[0085] 2. Scanning electron microscopy analysis was performed on a scanning electron microscope (XL-30) purchased from FEI Company, USA.

[0086] 3. The nitrogen adsorption-desorption experimental conditions include: Autosorb-1 nitrogen adsorption-desorption instrument from Quantachrome, USA, and degassing of samples at 200°C for 4 hours. All raw materials are chemically pure.

[0087] Example 1

[0088] 1.0 g of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene and 1.69 g of ethanol were added to 28 mL of acetic acid and sodium acetate buffer solution (pH = 4.4), and stirred at 15°C until polyoxyethylene-polyoxypropylene-polyoxyethylene was completely dissolved. Then 6 g of trimethylpentane was added to the above solution, and stirred at 15°C for 8 hours. Then 2.13 g of tetramethoxysilane was added to the above solution, and stirred at 15°C for 20 hours. The solution was transferred to a polytetrafluoroethylene-lined reactor, and after oven crystallization at 60°C for 24 hours, it was filtered and washed with distilled water to obtain No. 1 mesoporous clay silica filter cake.

[0089] Add hexadecyltrimethylammonium bromide and tetraethyl orthosilicate into an aqueous ammonia solution, and the molar ratio of tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, ammonia and water in an ammonia solution (25wt%) is 1:0.37:2.8:142. Stir at 50°C until dissolved, filter the solution and obtain a mesoporous clay material filter cake. Wash the filter cake until the pH is 7 to obtain a No. 2 mesoporous clay silica filter cake.

[0090] A 15 wt % water glass and a 12 wt % sulfuric acid solution were reacted for 1.5 hours at a water glass: sulfuric acid weight ratio of 5:1, the pH was adjusted to 3 with 98 wt % sulfuric acid, and the reaction material was filtered and washed with distilled water until the sodium ion content was 0.02 wt %, to obtain a silica gel filter cake.

[0091] Put 10 grams of the prepared No. 1 mesoporous clay silica filter cake, 10 grams of No. 2 mesoporous clay silica filter cake, 10 grams of silica gel filter cake and 10 grams of pyrophyllite clay mineral powder into a 100 mL ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3 mm, the number is 1, and the rotation speed is 400 r / min. Close the ball mill, and ball mill at a temperature of 60°C in the ball mill for 1 hour to obtain 26 grams of solid powder; dissolve the solid powder in 30 grams of deionized water, and spray dry at 200°C and a rotation speed of 12000 r / min; calcine the product obtained after spray drying at 500°C in a muffle furnace for 24 hours to remove the template agent, and obtain 24 grams of the target product carrier with the template agent removed, named JKGJYL. The scanning electron microscope photo of the carrier is shown as follows Figure 1 The X-ray diffraction pattern is shown in Figure 2 The structural parameters are shown in Table 1.

[0092] 0.3407 g of activated (under nitrogen protection, the carrier was heated at 500° C. for 24 hours) JKGJYL was transferred to a 250 ml glass reactor fully replaced with nitrogen, 20 ml of refined toluene (refluxed through sodium for 24 hours) and 0.4 g of methylaluminoxane were added, and stirred at 50° C. for 4 hours. After the reaction was completed, it was allowed to stand, the liquid was filtered out after stratification, and the solid was washed three times with 20 ml of hexane, and finally the solid was blown dry with nitrogen to obtain JKGJYL loaded with methylaluminoxane (named MAO / JKGJYL).

[0093] Under nitrogen protection, MAO / JKGJYL was added to a 250 ml glass reactor, 20 ml of refined toluene (refluxed through sodium for 24 hours) was added, 15.6 mg of bis(n-butylcyclopentadienyl)zirconium dichloride was added dropwise at 30°C, and the reaction was stirred for 0.5 hours. After the reaction was completed, the reaction was allowed to stand, the liquid was filtered out after stratification, the solid was washed three times with 10 ml of toluene, then washed twice with 40 ml of hexane, and the solid was dried with nitrogen to obtain a supported metallocene catalyst (named JKGJYL-BU). The structural parameters of the catalyst are shown in Table 1.

[0094] Application Example 1

[0095] In a 2-liter stainless steel high-pressure polymerization autoclave, nitrogen and ethylene were replaced three times each, then 200 ml of hexane was added, the autoclave temperature was raised to 80°C, and 800 ml of hexane was added. Along with the addition of hexane, 2 ml of 1 mol / L triethylaluminum hexane solution was added, followed by 43.3 mg of JKGJYL-BU, ethylene was introduced to raise the pressure to 1.0 MPa and maintained at 1.0 MPa, and the reaction was carried out at 70°C for 1 hour. The efficiency of the catalyst was determined to be 2000 g PE / gcat·h.

[0096] Application Example 2

[0097] In a 2-liter stainless steel high-pressure polymerization autoclave, nitrogen and ethylene were replaced three times each, then 200 ml of hexane was added, the autoclave temperature was raised to 80°C, and 800 ml of hexane was added. Along with the addition of hexane, 2 ml of 1 mol / L triethylaluminum (TEA) hexane solution and 10 ml of hexene were added, followed by 40.3 mg of JKGJYL-BU, ethylene was introduced to raise the pressure to 1.0 MPa and maintained at 1.0 MPa, and the reaction was carried out at 70°C for 1 hour. The efficiency of the catalyst was determined to be 3000 g PE / gat·h by calculation.

[0098] Comparative Example 1

[0099] ES955 silica gel was calcined at 400°C for 10 hours under nitrogen protection to remove hydroxyl groups and residual moisture, thereby obtaining heat-activated ES955 silica gel.

[0100] Under nitrogen protection, 0.9 g of ES955 silica gel was reacted with 1.0 g of methylaluminoxane and 10 mL of toluene (refluxed through sodium for 24 hours) at 50°C with stirring for 4 hours. The solid was washed three times with toluene and three times with 20 mL of hexane. Finally, the solid was dried with nitrogen to obtain ES955 loaded with methylaluminoxane (named MAO / ES955).

[0101] Under nitrogen protection, MAO / ES955 was added to a 250 ml glass reactor, 20 ml of refined toluene (refluxed for 24 hours via sodium) was added, 49 mg of metallocene catalyst precursor bis(n-butylcyclopentadienyl)zirconium dichloride was added dropwise at 30°C, and the reaction was stirred for 0.5 hours. After the reaction was completed, the reaction was allowed to stand, the liquid was filtered out, the solid was washed three times with 10 ml of toluene, then washed twice with 40 ml of hexane, and the solid was blown dry with nitrogen to obtain a supported metallocene catalyst (named ES955-BU).

[0102] Comparative Example 2

[0103] The difference from Example 1 is that the carrier does not contain pyrophyllite clay mineral powder, and no pyrophyllite clay mineral powder is added during ball milling. The rest is the same as Example 1, and the obtained catalyst is JKGJ-BU.

[0104] Comparative Example 3

[0105] The difference from Example 1 is that the carrier does not contain silica gel and pyrophyllite clay mineral powder, and silica gel and pyrophyllite clay mineral powder are not added during ball milling. The rest is the same as Example 1, and the obtained catalyst is JK-BU.

[0106] Application Comparative Example 1

[0107] The homopolymerization of ethylene was carried out in the same manner as in Application Example 1, except that the catalyst used was ES955-BU prepared in Comparative Example 1. The efficiency of the catalyst was determined to be 694 gPE / gcat·h.

[0108] Application Comparative Example 2

[0109] Ethylene and hexene were copolymerized by the same method as in Application Example 2, except that the catalyst used was ES955-BU prepared in Comparative Example 1. The efficiency of the catalyst was determined to be 1361 g PE / gcat·h.

[0110] Application Comparative Example 3

[0111] The homopolymerization of ethylene was carried out in the same manner as in Application Example 1, except that the catalyst used was JKGJ-BU prepared in Comparative Example 2. The efficiency of the catalyst was determined to be 1200 gPE / gcat·h.

[0112] Application Comparative Example 4

[0113] Ethylene and hexene were copolymerized by the same method as in Application Example 2, except that the catalyst used was JKGJ-BU prepared in Comparative Example 2. The efficiency of the catalyst was determined to be 1000 g PE / gcat·h.

[0114] Application Comparative Example 5

[0115] The homopolymerization of ethylene was carried out in the same manner as in Application Example 1, except that the catalyst used was JK-BU prepared in Comparative Example 3. The efficiency of the catalyst was determined to be 1300 gPE / gcat·h.

[0116] Application Comparative Example 6

[0117] Ethylene and hexene were copolymerized by the same method as in Application Example 2, except that the catalyst used was JK-BU prepared in Comparative Example 3. The efficiency of the catalyst was determined to be 1100 gPE / gcat·h.

[0118] Table 1

[0119]

[0120] From the data in Table 1, it can be seen that the pore structure parameters of JKGJYL-BU are lower than those of JKGJYL, indicating that methylaluminoxane and metallocene compounds do enter the pores of JKGJYL.

[0121] from Figure 1 From the scanning electron microscope photo, we can see that the microscopic morphology of JKGJYL is spherical. Figure 2 It can be clearly seen from the XRD spectrum that JKGJYL has a diffraction peak in the small angle area.

[0122] From the data of the application examples and the comparative examples, it can be seen that the activities of the supported metallocene catalyst provided by the present invention in catalyzing the homopolymerization and copolymerization of ethylene are 2000 g PE / gcat·h and 3000 g PE / gcat·h, respectively, while the activities of the supported metallocene catalyst in catalyzing the homopolymerization and copolymerization of ethylene using the same active component supported by 955 silica gel commonly used in industry are 694 g PE / gcat·h and 1361 g PE / gcat·h, respectively. The activity of the catalyst of the present invention is higher.

[0123] In addition, the catalyst of the present invention has a higher catalytic activity than a carrier without adding pyrophyllite clay mineral powder. The catalyst of the present invention has a higher catalytic activity than a carrier without adding silica gel and pyrophyllite clay mineral powder.

[0124] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A supported metallocene catalyst, characterized in that: The catalyst comprises a carrier and a metallocene compound and an alkylaluminoxane loaded on the carrier; the carrier is a spherical pyrophyllite clay mineral mesoporous clay composite material with three-dimensional cubic channels made of mesoporous clay silica, silica gel and pyrophyllite clay mineral; the metallocene compound has a structure shown in Formula 1, In Formula 1, R1, R2, R3, R4, R5, R1', R2', R3', R4' and R5' are each independently hydrogen or a C1-C5 alkyl group, and at least one of R1, R2, R3, R4 and R5 is a C1-C5 alkyl group, at least one of R1', R2', R3', R4' and R5' is a C1-C5 alkyl group, M is one of titanium, zirconium and hafnium, and X is a halogen.

2. The supported metallocene catalyst according to claim 1, wherein In Formula 1, R1 and R1' are each independently a C1-C5 alkyl group, R2, R3, R4, R5, R2', R3', R4' and R5' are all hydrogen; R1 and R1' are each independently preferably n-butyl or tert-butyl, more preferably n-butyl; M is zirconium; X is chlorine or bromine, preferably chlorine.

3. The supported metallocene catalyst according to claim 1, wherein The alkyl group in the alkylaluminoxane is a C1-C5 alkyl group, and the alkylaluminoxane is preferably methylaluminoxane.

4. The supported metallocene catalyst according to claim 1, wherein The carrier has an average particle size of 30-60 microns, a specific surface area of ​​150-600 square meters / gram, a pore volume of 0.5-1.5 milliliters / gram, and a most probable pore size of 2-4, 5-15 and 10-40 nanometers.

5. The supported metallocene catalyst according to claim 1 or 4, wherein The preparation method of the carrier comprises the following steps: 1) in the presence of a template, trimethylpentane and ethanol, tetramethoxysilane is contacted with an acid agent, and the product obtained after the contact is crystallized and filtered to obtain a mesoporous clay silica filter cake No. 1; hexadecyltrimethylammonium bromide, ethyl orthosilicate and ammonia water are contacted, and the product after the contact is filtered to obtain a mesoporous clay silica filter cake No. 2; 2) contacting water glass with an inorganic acid, and filtering the product obtained after the contact to obtain a silica gel filter cake; 3) mixing and ball-milling the No. 1 mesoporous clay silica filter cake, the No. 2 mesoporous clay silica filter cake, the silica gel filter cake and the pyrophyllite clay mineral powder; 4) The solid powder obtained after ball milling is slurried with water and then spray-dried, and then the template in the obtained product is removed to obtain the carrier.

6. The supported metallocene catalyst according to claim 5, wherein In step 1), the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene, the acid is a buffer solution of acetic acid and sodium acetate with a pH value of 1-6; the molar ratio of the template, ethanol, trimethylpentane and tetramethoxysilane is 1:100-500:200-600:50-200; the molar ratio of ammonia to water in the tetraethyl orthosilicate, hexadecyltrimethylammonium bromide and ammonia water is 1:0.1-1:0.1-5:100-200; The conditions for contacting tetramethoxysilane with the acid agent include: temperature of 10-60°C, time of 10-72 hours, and pH value of 1-7; the conditions for crystallization include: temperature of 30-150°C, time of 10-72 hours; the conditions for contacting hexadecyltrimethylammonium bromide, ethyl orthosilicate and ammonia water include: temperature of 25-100°C, time of 1-10 hours.

7. The supported metallocene catalyst according to claim 5, wherein In step 2), the inorganic acid is one or more of sulfuric acid, nitric acid and hydrochloric acid; The conditions for contacting the water glass with the inorganic acid include: a temperature of 10-60° C., a time of 1-5 hours, and a pH value of 2-4.

8. The supported metallocene catalyst according to claim 5, wherein In step 3), based on 100 parts by weight of the total amount of the No. 1 mesoporous clay silica filter cake and the No. 2 mesoporous clay silica filter cake, the amount of the silica gel filter cake is 20-150 parts by weight, and the amount of the pyrophyllite clay mineral powder is 20-150 parts by weight; the weight ratio of the No. 1 mesoporous clay silica filter cake to the No. 2 mesoporous clay silica filter cake is 0.5-1.5:

1.

9. The supported metallocene catalyst according to claim 1, wherein Based on the total weight of the supported metallocene catalyst, the total amount of the metallocene compound and the alkylaluminoxane is 10-60% by weight, preferably 45-55% by weight, the content of the carrier is 40-90% by weight, 45-55% by weight; the molar ratio of aluminum in the alkylaluminoxane to M in the metallocene compound is 10-300:1, preferably 15-250:1, more preferably 15-200:

1.

10. The method for preparing a supported metallocene catalyst according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: (1) contacting the carrier with alkylaluminoxane in a solvent under the protection of an inert gas, and then removing the solvent to obtain a carrier loaded with alkylaluminoxane; (2) Under the protection of an inert gas, the carrier loaded with alkylaluminoxane is contacted with a metallocene compound in a solvent, and the solvent is removed to obtain the supported metallocene catalyst.

11. The method for preparing a supported metallocene catalyst according to claim 10, wherein: The contact conditions in step (1) include: a contact time of 1-10 hours, preferably 2-6 hours; a contact temperature of 25-80° C., preferably 30-60° C.; The contact conditions in step (2) include: contact time of 0.3-2 hours, preferably 0.4-1 hour; contact temperature of 25-80°C, preferably 25-50°C.

12. Use of the supported metallocene catalyst according to any one of claims 1 to 9 in olefin polymerization.

Citation Information

Patent Citations

  • Supported metallocene catalyst and preparation method therefor

    CN105524193A

  • Spherical zeolite mesoporous composite material and supported catalyst, preparation method and application of spherical zeolite mesoporous composite material, and method for polymerizing alkene

    CN106554432A

  • Process for producing olefin polymer

    CN1160059A